Peran Guru Penggerak Dalam Penguatan Profil Pelajar Pancasila (Kajian Study Literatur) - Susi Susi; Ria Agustina; Miftahul Janah; Siti Mayang Sari; Diana Sartika; Anisa Agustanti (Departement of Mathematics Education, 2023)
The Role of the Movement Teacher In Realizing Profile Of Pancasila In School. In the current era, there are four major challenges in the world of education, including problems related to the noble values and morals of the nation; the need for maturity to become a citizen; support the realization of social justice and the creation of 21st century competence. To face these challenges, the government established a Teacher Motivator program to launch the Pancasila Student Profile. The goal of this research was to uncovered the role of the teacher in the development of students’ profiles at Pancasila in order to realized resilience in character education in the twenty-first century so that Indonesians could compete globally. What were the rights and responsibilities of a teacher-mover in carrying out the process of education to strengthened the profile of students in Pancasila. What importance should the master drive had in realizing the resilience of character education in the twenty-first century. This was a normative study; the research phase of the study of literature and the deductive analysis. The conceptual approach and the legislative approach were two types of research approaches used by researchers. Researchers conducted research on what the role of the teacher was in the effort to strengthened the profile of Pancasila students on the students as an effort to resilience character education in the twenty-first century. Researchers were also employing the literature method and interview with teacher. . The results of this study were the Master Drive had an important role in shaping the resilience of the character of their students. Such a role, which was to became the leader of learning that encourages the well- being ecosystem education in schools, moving the learning community (to the practitioner community) for co-teachers in the school and in its territory, becoming a teacher practice (coach) for his other teacher related to the development of learning in schools, Open space discussions and positive space of collaboration between teachers and stakeholders in and outside of school to improved the quality of learning, and encourage the improvement of students ‘ leadership in school.